A review of optic perineuritis - Tai , Evelyn Li Min; Tevaraj, Jessica Mani Penny; Thavaratnam, Lakana Kumar; Mohd Noor, Raja Azmir; Win Mar , Salmah; Wan Hitam, Wan Hazabbah (Press of International Journal of Ophthalmology, 2017)
Optic perineuritis ( OPN ) refers to a spectrum of conditions involving pathologic inflammation of the optic nerve sheath. The classic triad of OPN consists of unilateral optic neuropathy associated with pain and/or disc oedema, but the condition often mimics other optic neuropathies, resulting in delayed diagnosis and suboptimal treatment. We performed a database search of Medline and Ovid in January 2016 for articles published in any language with the keywords ‘optic perineuritis蒺. Sixty articles were found, published from 1956 to 2015. Two reviewers (Tai ELM and Tevaraj JMP) performed an independent screening of abstracts. Articles of interest were subsequently examined. In this review, we highlight the salient features of OPN, with particular emphasis on the clinical differences between OPN and optic neuritis. Although the majority of cases of OPN are idiopathic, investigations are required to rule out specific infectious and inflammatory causes of secondary OPN. MRI is an invaluable component of the workup, as radiographic demonstration of peri - neural inflammation is diagnostic of OPN. Corticosteroid therapy results in dramatic and rapid reversal of the signs and symptoms, but prolonged therapy with slow tapering of oral corticosteroids may be necessary to reduce the risk of relapses.